Green synthesis of reduced graphene oxide grafted Ag/ZnO for photocatalytic abatement of methylene blue and antibacterial activities. Issue 5 (October 2020) - Belachew, Neway; Kahsay, Mebrahtu Hagos; Tadesse, Aschalew; Basavaiah, Keloth
Graphical abstract: Highlights: A facile, green synthesis approach was used to synthesis RGO-Ag/ZnO nanocomposites successfully using L-Methionine . RGO-Ag/ZnO photocatalyst can effectively degrade methylene blue. RGO-Ag/ZnO shows strong antibacterial activity against B. Subtilis and E. coli . Abstract: We have reported a facile, green synthesis of reduced graphene oxide (RGO) grafted Ag/ZnO (RGO-Ag/ZnO) nanocomposite in the presence of L-Methionine (L-Met) for synergetic photocatalytic degradation of methylene blue (MB) and antibacterial activities. L-Met shows an excellent efficiency as stabilizing and reducing agents for the synthesis of both Ag NPs and RGO. The successful synthesis of pure phase L-Met-RGO-Ag/ZnO was confirmed by XRD. According to UV-DRS analysis, the doping of Ag resulted in a decrease bandgap energy of ZnO from 3.34 eV to 3.18 eV. The mixed morphologies of the nanocomposite were studied by SEM and TEM. The photocatalytic degradation efficiency of L-Met-RGO-Ag/ZnO towards MB dye was investigated at varying initial concentrations of MB dye, H2 O2, and ultrasonication. The optimum degradation efficiency of the nanocomposite (50 mg) at room temperature (25 °C) was found to be 99% with an initial MB dye concentration of 10 mg/L and 120 min contact time. The fast degradation of MB dye was observed in the presence of H2 O2 . The ultrasonication of the catalyst vanishes the synergetic interface of the nanocomposite, as a result, poor photocatalytic performance (85%) was observed even at a long period of contact time (210 min). Moreover, RGO-Ag/ZnO nanocomposites have shown strong antibacterial activity against both Gram-positive bacteria ( B. Subtilis) and Gram-negative bacteria ( E. coli) . In conclusion, RGO-Ag/ZnO nanocomposite shows a promising photocatalyst for the degradation of organic dyes and antibacterial activities.